Urinary tract infection caused by Enterococcus gallinarum in a 65-year-old female patient: Case report and review of literature (Indian Journal of Case Reports, 2025)
Urinary tract infection (UTI) is very common in adult females. Enterococcus spp. is an uncommon cause of UTI in females. They are sometimes resistant to vancomycin and make treatment difficult and prolonged. Enterococcus gallinarum is exceedingly rare as a uropathogen and can often be missed if not meticulously looked for. We here report a case of recurrent UTI due to E. gallinarum in a female diabetic patient aged 65 years, with confirmation of the isolate done by conventional as well as automated methods.